SCFSLF-mediated cytosolic degradation of S-RNase is required for cross-pollen compatibility in S-RNase-based self-incompatibility in Petunia hybrida - Liu, Wei; Fan, Jiangbo; Li, Junhui; Song, Yanzhai; Li, Qun; Zhang, Yu'e; Xue, Yongbiao (Frontiers in Genetics, 2014)
Many flowering plants adopt self-incompatibility (SI) to maintain their genetic diversity. In species of Solanaceae, Plantaginaceae and Rosaceae, SI is genetically controlled by a single S-locus with multiple haplotypes. The S-locus has been shown to encode S-RNases expressed in pistil and multiple SLF (S-locus F-box) proteins in pollen controlling the female and male specificity of SI, respectively. S-RNases appear to function as a cytotoxin to reject self-pollen. In addition, SLFs have been shown to form SCF (SKP1/Cullin1/F-box) complexes to serve as putative E3 ubiquitin ligase to interact with S-RNases. Previously, two different mechanisms, the S-RNase degradation and the S-RNase compartmentalization, have been proposed as the restriction mechanisms of S-RNase cytotoxicity allowing compatible pollination. In this study, we have provided several lines of evidence in support of the S-RNase degradation mechanism by a combination of cellular, biochemical and molecular biology approaches. First, both immunogold labeling and subcellular fractionation assays showed that two key pollen SI factors, PhSLF-S3L and PhSSK1 (SLF-interacting SKP1-like1) from Petunia hybrida, a Solanaceous species, are co-localized in cytosols of both pollen grains and tubes. Second, PhS3L-RNases are mainly detected in the cytosols of both self and non-self pollen tubes after pollination. Third, we found that both PhS3-RNases and PhS3L-RNases directly interact with PhSLF-S3L by yeast two-hybrid and co-immunoprecipitation assays. Fourth, S-RNases are specifically degraded in compatible pollen tubes by non-self SLF action. Taken together, our results demonstrate that SCFSLF-mediated non-self S-RNase degradation occurs in the cytosol of pollen tube through the ubiquitin/26S proteasome system serving as the major mechanism to neutralize S-RNase cytotoxicity during compatible pollination in P. hybrida.